HUBUNGAN MODAL PSIKOLOGIS DAN MOTIVASI KERJA GURU SMA NEGERI DI KABUPATEN PATI (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of research is to analyze the relationship of capital work motivation psychological teacher of state high school at pati regency. The population in this study was the civil servants of high school teacher’s in Pati regency. By using the proportional method samples studied a number of 183 respondents. The results of this study were (1) there is a strong and significant relationship between optimism and achievement motivation, (2) there is a strong and significant relationship between expectation and achievement motivation, (3) there is a strong and significant relationship between resilience and achievement motivation, (4) there is a strong and significant relationship between optimism and motivation to power, (5) there is a strong and significant relationship between the expectations of the ruling motivation, (6) there is a strong and significant relationship between resistance to motivation for power (7) there is a strong and significant relationship between optimism with affiliation motivation, (8) no relationship strong and significant correlation between expectations with affiliation motivation, (9) there is a strong and significant relationship between resistance to affiliation motivation. Keywords:   optimism, hope, resilience, motivation for achievement, motivation for power, motivation to affiliate.